T TANTANGAN SDM DI ERA GLOBALISASI - Mahisa, Rusman Alimin (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Abstract. Globalization brings changes in various fields of life, and the most felt in the field of human resources (HR). The impact of this HR change will be a shift in the composition of the labor market, where jobs will be lost but new jobs will emerge. According to the World Economic Forum estimates that around 65% of children entering primary school today will be working in completely new types of jobs. While many jobs or specialties that are in demand will decrease since 10 years ago. But entrepreneurs are starting to have the main goal to increase labor productivity, and innovation. They seek new, scarce skills, are willing to attract and retain people in their organizations who demonstrate a defensive attitude, responsiveness to change, an entrepreneurial mindset, and a desire to innovate. However, this is not the case in the existing labor market because it will be dominated by millennials, and will work together with Generation X, who will then retire or no longer work. The female and immigrant labor force will be more present in the labor market. In the digital world, the boundaries between work life and professional life will become blurred. Personal well-being and professionalism will be important. Departments and HR are facing new challenges. In this paper, a review of the relevant literature is carried out, to identify the changing challenges faced in the labor market, as well as what actions can be taken to increase the knowledge, skills, and attitudes needed in today's society. Another goal is to create a model that becomes a motivating factor, and involves the workforce. Keywords: Leadership, Management, HR, Globalization, .